2016
DOI: 10.1111/bcp.12932
|View full text |Cite
|
Sign up to set email alerts
|

Plant cystine‐knot peptides: pharmacological perspectives

Abstract: Cystine-knot miniproteins are a class of 30-50 amino acid long peptides widespread in eukaryotic organisms. Due to their very peculiar three-dimensional structure, they exhibit high resistance to heat and peptidase attack. The cystine-knot peptides are well represented in several plant species including medicinal herbs and crops. The pharmacological interest in plant cystine-knot peptides derives from their broad biological activities, mainly cytotoxic, antimicrobial and peptidase inhibitory and in the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 84 publications
0
37
0
2
Order By: Relevance
“…Plant knottins contain 30 amino acids and comprises inhibitors of α-amylase, trypsin and carboxypeptidase families as well as cyclotides. They perform several functions like enzyme-inhibitory, cytotoxic, antimicrobial, insecticidal and anti-HIV activities [72,73]. Initially, it was identified as protease inhibitors [74].…”
Section: Knottin-type Peptidesmentioning
confidence: 99%
“…Plant knottins contain 30 amino acids and comprises inhibitors of α-amylase, trypsin and carboxypeptidase families as well as cyclotides. They perform several functions like enzyme-inhibitory, cytotoxic, antimicrobial, insecticidal and anti-HIV activities [72,73]. Initially, it was identified as protease inhibitors [74].…”
Section: Knottin-type Peptidesmentioning
confidence: 99%
“…Contrary to the α-helical peptides, those that adopt the β-sheet conformations contain at least two Cys residues that form between 1 and 5 intramolecular disulfide bonds [ 60 ] that stabilize the tertiary structure of the peptides and confer substantial resistance to heat, protease and enzymatic inactivation [ 61 , 62 ]. β-hairpin structures are also common for those containing 2–4 Cys residues e.g., protegrin-1 [ 63 ].…”
Section: Diverse Sources Of Ampsmentioning
confidence: 99%
“…PIs are crucial components for cellular homeostasis and survival, and participate in several physiological processes, such as the mobilization of storage proteins in seeds, the regulation of endogenous enzymatic activities, and the protection against pests [2,3]. In addition to proteins with higher molecular mass such as serpins, the PI group comprises small/medium range polypeptides (<15 kDa), which include inhibitors of metallocarboxypeptidase and cyclotides [1,4]. Small polypeptide-based PIs are generally composed by a single domain including specific secondary structural elements and disulfide bridges.…”
Section: Introductionmentioning
confidence: 99%
“…The C-terminal glycine (Gly39) of the PCI is cleaved-off by the protease exposing Val38, whose carboxylate group coordinates with Zn 2+ in the protease active site, blocking catalytic activity [7,9].Plant cystine-knot metallocarboxypeptidase inhibitors possess bioactivity also in mammalian cells, since they can target human growth factor receptors either acting as an antagonist of growth factor for receptor binding or by altering their signal transduction pathways [5,[10][11][12]. Due to their bioactivity and highly-stable structural scaffold, cystine-knot proteins have received great attention for pharmacological application to develop diagnostic markers and therapeutic agents (for a review see [4]). Regarding the role of cystine-knot proteins in plants, it was demonstrated that PCIs accumulate in potato tubers and in leaves after wounding [13,14] and after treatment with abscisic acid (ABA) and jasmonate [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation